Scientific evidence about the effects of physical exercise on old bone mineral density (Research, Society and Development, 2020)
Introduction: Physical exercise is indicated as a prophylactic measure in the treatment of osteoporosis, decreasing the loss of bone mass, as well as, in some cases providing its remodeling. Objective: To analyze, through a systematic review, the scientific evidence about the effects of physical exercise on bone mineral density in the elderly. Method: This is a study of systematic review of the literature, carried out in the databases SciELO, BVS, PubMed, Web of Science through controlled descriptors, Elderly, Exercise and Bone Mineral Density, as well as their translations into Spanish and English, according to DeCS and Mesh, published between 2014 and 2019. Results: Taking into account the Exercise Protocol, the most applied tests were, Dual Energy X-Ray (DXA) with 66.66% following by calculating the body mass index (BMI) with 22.22%, in addition to the walking tests, Clinical Falls Risk Assessment Instrument (QuickScreen), Timed Up and Go (TUG), Functional Reach Test (FRT), 1 maximum repetition (1RM), vertical vibration Fitvibe Excel Pro platform, all with 11.12%. It is worth mentioning that there was a significant relationship between physical exercise and the increase in BMD, in the selected studies. Conclusion: According to the results obtained in this review, we can conclude that physical exercise plays a significant role in the prophylaxis and treatment of osteoporosis.